2018
DOI: 10.1590/1679-78254574
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Post-Northridge Welded Connections

Abstract: Post-Northridge welded connections are widely used in engineering projects as lateral-force-resisting systems. In this study, we aim to assess the cyclic performance of the post-Northridge welded connections to compare the connections with each other. For this purpose, we focus on Welded Unreinforced Flange-Welded Web (WUF-W), Welded Flange Plate (WFP) and Reduced Beam Section (RBS) connections. ANSYS Finite Element Analysis (FEA) software is used to do this investigation and evaluate the adequacy of the numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…di Sarno et al [21] conducted a numerical study on the case studies in Amatrice, Central Italy, which were moment resisting frame buildings and suggested possible improvements. Cyclic performance of post-Northridge welded connections was assessed by Yilmaz and Bekiroglu [22] in ANSYS software. Reduced Beam Section (RBS), Welded Unreinforced Flange -Welded Web (WUF-W), and Welded Flange Plate (WFP) connections were evaluated, and it was concluded that high stiffness and high safety belong to WFP and RBS connections, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…di Sarno et al [21] conducted a numerical study on the case studies in Amatrice, Central Italy, which were moment resisting frame buildings and suggested possible improvements. Cyclic performance of post-Northridge welded connections was assessed by Yilmaz and Bekiroglu [22] in ANSYS software. Reduced Beam Section (RBS), Welded Unreinforced Flange -Welded Web (WUF-W), and Welded Flange Plate (WFP) connections were evaluated, and it was concluded that high stiffness and high safety belong to WFP and RBS connections, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the application of the RBS method to the beam flanges, the fracture still occurs in close proximity of the connection in some instances [14]. In 2018, Yilmaz and Bekiroglu [15] conducted research regarding improved connections, consisting of steel connections with Cover Plates and RBS. The panel zone performance and damping performance of connections with Cover Plates are inadequate.…”
Section: Introductionmentioning
confidence: 99%